1996
DOI: 10.1016/0735-1097(96)00167-2
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-head comparison of exercise-redistribution-reinjection thallium single-photon emission computed tomography and low dose dobutamine echocardiography for prediction of reversibility of chronic left ventricular ischemic dysfunction

Abstract: Quantitative exercise-redistribution-reinjection thallium SPECT and dobutamine echocardiography have comparable accuracy for prediction of reversibility of global left ventricular dysfunction after revascularization. However, dobutamine echocardiography has greater specificity than thallium imaging for prediction of functional recovery on a segmental basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(46 citation statements)
references
References 31 publications
3
40
1
2
Order By: Relevance
“…In a subgroup of 43 patients with viable myocardium included in this study, we had previously shown that revascularization improved global LV ejection fraction by an average of 13%, a change that is likely to impact survival. 8 In contrast, in 30 patients with nonviable myocardium, revascularization did not result in any significant changes in global LV function and barely prevented LV dilatation. 8 Likewise, in the present study, revascularization had no major influence on long-term outcome in the absence of viable myocardium.…”
Section: Prognostic Implications Of Myocardial Ischemia and Viabilitymentioning
confidence: 81%
See 4 more Smart Citations
“…In a subgroup of 43 patients with viable myocardium included in this study, we had previously shown that revascularization improved global LV ejection fraction by an average of 13%, a change that is likely to impact survival. 8 In contrast, in 30 patients with nonviable myocardium, revascularization did not result in any significant changes in global LV function and barely prevented LV dilatation. 8 Likewise, in the present study, revascularization had no major influence on long-term outcome in the absence of viable myocardium.…”
Section: Prognostic Implications Of Myocardial Ischemia and Viabilitymentioning
confidence: 81%
“…Until now, studies addressing the contribution of these techniques to the detection and treatment of viable myocardium have mainly concentrated on their ability to predict the return of contractile function after revascularization. [5][6][7][8] The purpose of the present study was to establish the potential prognostic implications of identifying viable and/or ischemic myocardium by either of these 2 methods in patients with LV ischemic dysfunction. The results can be summarized as follows:…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations